Efficacy of Agmatine Treatment in Experimental Acute Pancreatitis Rat Model - Yeniçeri, Murat; Tanoğlu, Alpaslan; Salmanoğlu, Musa; Çırak, Zafer; Şenoymak, Mustafa Can; Baş, Süleyman; Gökçen, Ayşe Sade (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Acute pancreatitis which is characterized by pancreatic inflammation can sometimes be difficult to treat because of limited therapeutic options. The purpose of the study was to assess the effects of agmatine in the acute pancreatitis experimental rat model. Materials and Methods: An acute pancreatitis model was created with the administration of cerulein in 40 female Sprague–Dawley rats. Agmatine was administered as a protective agent at 5 mg/kg (low dose) and 10 mg/kg (high dose). The rats were divided into 5 groups, each with 8 rats: group 1 (acute pancreatitis); group 2 (acute pancreatitis + low-dose agmatine 5 mg/kg); group 3 (acute pancreati tis + high-dose agmatine 10 mg/kg); group 4 (placebo, acute pancreatitis + saline); and group 5 (sham and saline infusion). All rats were sacrificed 24 hours after the last injection, and the levels of superoxide dismutase, interleukin-1 beta, and tumor necrosis factor-alpha were assessed in blood samples collected via cardiac puncture. Histopathological examination was performed by a pathologist, who was blind to the groups, according to the Schoenberg’s pancreatitis scoring index. Results: The amylase (16.67 and 37.89 U/L), glutathione peroxidase (13.62 and 18.44 ng/mL), tumor necrosis factor-α (39.68 and 64 ng/mL), interleukin-1 (484.73 and 561.83 pg/mL), and transforming growth factor-β (110.52 and 126.34 ng/L) levels were significantly lower and superoxide dismutase (1.29 and 0.98 ng/L) and malondialdehyde (0.99 and 0.96 nmol/mL) levels were significantly higher ingroup 3 compared to group 1 (P < .05). Moreover glutathione peroxidase, tumor necrosis factor-α, and transforming growth factor-β levels were lower, and malondialdehyde levels were higher in the group 3 compared to group 2 (P < .05). Although the Schoenberg’s pan creatitis scoring index was not significantly different between the high- and low dose treatment groups, rats who received high-dose treatment had significantly lower scores compared to those with acute pancreatitis group. Conclusion: This is the first study that evaluated the efficacy of agmatine in an experimental model of acute pancreatitis. Agmatine, an anti-inflammatory and antioxidant agent, had a protective effect in an experimental rat model of acute pancreatitis. Cite this article as: Yeniçeri M, Tanoğlu A, Salmanoğlu M, et al. Efficacy of agmatine treatment in experimental acute pancreatitis rat model. Turk J Gastroenterol. 2024;35(1):27-31.